M-CHOLINOLYTICS IN PREOPERATIVE PREPARATION OF CHILDREN WITH OBSTRUCTIVE UROPATHIES - S.N. Zorkin; T.N. Gusarova; S.A. Borisova (Union of pediatricians of Russia, 2008)
The article highlights the results of oxybutinin hydrochloride m cholinolytics application in children with disorders of the adaptive urinary bladder function against the obstructive uropathy during the preoperative preparation. It shows the efficiency and safety of the intravesical medication injection, which allowed the researchers to cut the preoperative period in children with a combined pathology of the upper urinary tracts and expand the age range for the application of the given medication.Key words: urinary bladder dysfunctions, obstructive uropathy, oxybutinin hydrochloride, preoperative preparation, children.